The reality of the development of the avocado and coffee trees intercrop model in Bao Lam district, Lam Dong province - Dang , Van Dong (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
According to study about the reality of the development of the avocado and coffee trees intercrop model in Bao Lam district, Lam Dong province, we propose some solutions to develop the intercropping avocado with coffee firmly in this region. The results show that the area of intercrop avocado with coffee in Bao Lam district tends to increase over the years. This model has positively impacted on the economy, society and environment of the region.